THE EFFECT OF WORKLOAD ON EMPLOYEE PERFORMANCE AT THE PURWOASRI COMMUNITY HEALTH CENTER, KEDIRI REGENCY IN 2025 - M Lutvi Irvan A.; Aris Dwi C.; Suryono; Cintya N (Suluh Adiluhung Publisher (SAPub), 2026)
Workload refers to the amount of work targets or outcomes that must be achieved within a specific unit of time, while performance denotes the results and behaviors exhibited in completing assigned tasks and responsibilities during a given period. Excessive workload among healthcare professionals, including nurses in Community Health Center, leads to difficulties in achieving optimal performance outcomes. Overlapping schedules between service delivery and health screening activities make task completion challenging, impacting performance reports and the achievement of Health Center program targets. This study aims to analyze the influence of workload on employee performance at Purwoasri Health Center, Kediri Regency in 2025. The research adopts a quantitative approach with a cross-sectional design. The population comprises all employees at Purwoasri Health Center, totaling 44 respondents. Non-probability sampling (Saturation Sampling) was used to include all population members as samples. Data collection employed questionnaires, and data analysis utilized simple linear regression with SPSS v.22 for Windows. Based on the results of simple linear regression, the obtained significance value of 0.00 < 0.05 indicates a significant influence. In conclusion, workload has a positive and significant influence on employee performance. It is recommended that Health Center management conducts a reassessment of job descriptions to ensure tasks assigned align with each employee's capacities and skills.